EKSPERIMEN PEMBUATAN SUGAR PASTRY DENGAN SUBSTITUSI TEPUNG AMPAS TAHU - Erma Handarsari (Universitas Muhammadiyah Semarang, 2010)
Pastry Sugar is a small cake made from ingredients flour, margarine, powdered sugar, egg yolks and making done by the oven. To reduce the dependency of wheat flour in the making of sugar pastry flour tofu is used as substituents. This study aims to analyze the physical and chemical characteristic that include protein content (micro Kjedhal), moisture content (oven method), heavy metal (Cu) residues (AAS at 324.7 nm), and organoleptic characteristic. Data analysis using the Anava to know the difference in quality sugar pastry and then proceed to determine the value of Test Tukye Best of each sample. The results of research, the more substitutes tofu higher protein content. The highest organoleptic assessment is sugar pastry with flour substitute tofu waste 10%. Sugar pastry is the best (SNI meet No.01-2973-1992) contains 15% protein content, water content 1.56%, and 9.75 ppm Cu .. Key words: sugar pastry, substitution, flour tofu